2016
DOI: 10.1093/beheco/arw147
|View full text |Cite
|
Sign up to set email alerts
|

Brood size, telomere length, and parent-offspring color signaling in barn swallows

Abstract: Trade-offs select for optimal allocation of resources among competing functions. Parents are selected to maximize production of viable offspring by balancing between progeny number and "quality." Telomeres are nucleoproteins, at the ends of eukaryotic chromosomes, that shorten when cells divide. Because shortening below a certain threshold depresses organismal functioning and rate of shortening depends on environmental conditions, telomeres are good candidates as mediators of trade-offs. We altered brood size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 59 publications
(87 reference statements)
4
38
0
Order By: Relevance
“…However, the causes of telomere attrition are likely to differ for the two extremes. The negative effect of increased brood size on telomere length is in line with previous studies (Boonekamp et al., ; Costanzo et al., ; Nettle et al., ), probably as a consequence of developmental stress caused by increased sibling competition and reduced access to food. By contrast, nestlings raised in reduced broods were not constrained by these factors and therefore maximized their growth rates.…”
Section: Discussionsupporting
confidence: 90%
“…However, the causes of telomere attrition are likely to differ for the two extremes. The negative effect of increased brood size on telomere length is in line with previous studies (Boonekamp et al., ; Costanzo et al., ; Nettle et al., ), probably as a consequence of developmental stress caused by increased sibling competition and reduced access to food. By contrast, nestlings raised in reduced broods were not constrained by these factors and therefore maximized their growth rates.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been demonstrated that nestling vocalizations [37] and gape colouration [38] varies between the sexes. Recent studies have also revealed significant differences in ventral colour between nestling of either sex [88,89] and differential variation in parental care allocation in relation to offspring plumage colouration among males as compared to female nestlings [90]. The existence of sex-related variation in offspring post-hatching phenotype and of differential allocation to either sex by parents suggests that sex-dependent egg odour might pave the way to pre-hatching differential allocation of care by parents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, especially under high predation pressure, stonechats often skip a second clutch in favor of their fledglings (Scheuerlein et al, 2001). In addition, as environmental conditions and parental care during growth can influence telomere loss and maintenance (e.g., Costanzo et al, 2017), extended parental care may create more favorable conditions for tropical fledglings and juveniles that may allow them to maintain their telomeres better than temperate ones. A number of recent studies in temperate songbirds during the nestling period have shown that the rearing environment has an influence on telomere attrition rates in early life (e.g., Salmon et al, 2016;Soler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies in temperate songbirds during the nestling period have shown that the rearing environment has an influence on telomere attrition rates in early life (e.g., Salmon et al, 2016;Soler et al, 2017). For example, growing up in large broods, high begging effort and low food availability hasten telomere loss in nestlings (Costanzo et al, 2017;Nettle et al, 2017;Young et al, 2017 , 2014;Salmon et al, 2017). The effect of extended parental care in tropical birds on telomere dynamics in fledglings should be further investigated, for example through brood size manipulation experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation